Efektivitas Media Pembelajaran Animasi Interaktif pada Materi Ism al-Isyaarah dan Ism al-Mauṣhuul: The Effectiveness of Interactive Animation Learning Media in Ism al Isyaarah and Ism al-Maushuul Topics - Fandy Maulana Ihsan; Anwar Sidik (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2026)
This study aims to examine the effectiveness of interactive animated learning media in teaching Ism al-Isyārah and Ism al-Mawṣūl. This research is motivated by the low interest and understanding of students in learning Arabic, which is still dominated by conventional teaching methods. In addition, this study offers novelty as it is conducted in the Ujung Batu area, which has rarely been explored in Arabic language education research. The subjects of this study were 22 students of Sa’ad bin Abi Waqqash Islamic Boarding School in Ujung Batu, selected using a total sampling technique. This study employed a quantitative approach with a quasi-experimental method using a pretest-posttest design. The research instruments included tests to measure cognitive aspects and questionnaires to assess affective aspects. Data were collected through pretests, posttests, and questionnaires, and analyzed using a t-test to determine differences before and after treatment. The results showed that interactive animation media had a significant effect on students’ cognitive achievement and also had a positive impact on affective aspects, such as interest and learning motivation. Therefore, it can be concluded that interactive animated media is effective in improving both cognitive and affective domains. This study recommends the use of interactive animation media as an alternative to enhance the quality of Arabic language learning.